Growth and metabolism of Oenococcus oeni for malolactic fermentation under pressure. (17th October 2016) - Neto, R.; Mota, M.J.; Lopes, R.P.; Delgadillo, I.; Saraiva, J.A.
Abstract: Malolactic fermentation is a biological deacidification process of wine, characterized by the transformation ofl ‐malic acid tol ‐lactic acid and CO2 . Oenococcus oeni is able to perform malolactic fermentation and to survive under wine harsh conditions, representing great interest for wine industry. The aim of this work was to evaluate the effect of high pressure on the metabolism of O. oeni growing in culture media, regarding malolactic fermentation, sugars metabolism and bacterial growth. A pressure stress of 50 MPa during 8 h did not result in significant modifications in bacterial metabolism. In contrast, a stress of 100 MPa during 8 h resulted in lower amounts ofl ‐lactic acid, while higher amounts ofd ‐lactic acid were also registered, indicating changes in bacterial metabolism. A pressure stress of 0·5 MPa during 300 h resulted in complete inactivation of O. oeni, but malolactic fermentation was still observed at some extent, showing that malolactic enzyme was not completely inactivated at these conditions. It was concluded that high pressure causes modification of O. oeni metabolism, and possibly in enzyme activities. Significance and Impact of the Study: This study demonstrates that high pressure affects the viability and metabolism of Oenococcus oeni on a culture medium, depending on the pressure intensity and holding time applied. These effects were particularly noteworthy on malolactic fermentation. After high pressure (HP)‐stress of 100 MPa for 8 h, modifications in the activity of malolactic enzyme were detected, possibly due to a change in specificity. After a HP‐stress of 300 MPa for 0·5 h, malolactic enzyme showed some residual activity, although O. oeni was completely inactivated. This study provides relevant information about the impact of high pressure on malolactic fermentation, opening interesting possibilities to the improvement of biocatalytic processes. Abstract : Significance and Impact of the Study: This study demonstrates that high pressure affects the viability and metabolism of Oenococcus oeni on a culture medium, depending on the pressure intensity and holding time applied. These effects were particularly noteworthy on malolactic fermentation. After high pressure (HP)‐stress of 100 MPa for 8 h, modifications in the activity of malolactic enzyme were detected, possibly due to a change in specificity. After a HP‐stress of 300 MPa for 0·5 h, malolactic enzyme showed some residual activity, although O. oeni was completely inactivated. This study provides relevant information about the impact of high pressure on malolactic fermentation, opening interesting possibilities to the improvement of biocatalytic processes.